The tectono-stratigraphic evolution of distal, hyper-extended magma-poor conjugate rifted margins: Examples from the Alpine Tethys and Newfoundland–Iberia. - Decarlis, A; Manatschal, Gianreto; Haupert, I; Masini, Emmanuel (Marine and Petroleum Geology, 2015)
International audience